Respuesta :

Answer:

r = 4

Step by step explanation :

Step 1 : Add 13 to both sides.

4(r + 2) - 13 + 13 = 11 + 13

4(r + 2) = 24

Step 2 : Divide by 4 on both sides.

[tex]\frac{4(r+2)}{4} = \frac{24}{4}[/tex]

r + 2 = 6

Step 3 : Subtract 2 from both sides.

r = 4

The value of r is 4 in the given expression and this can be determined by using the arithmetic operation.

Given :

Expression -  4(r + 2) – 13 = 11

The following steps can be used to evaluate the given expression:

Step 1 - Write the expression.

4(r + 2) – 13 = 11

Step 2 - Add 13 on both sides in the above equation.

4(r + 2) – 13 + 13 = 11 + 13

4(r + 2)  = 24

Step 3 - Multiply 4 by (r + 2) in the above expression.

4r + 8 = 24

Step 4 - Subtract 8 on both sides in the above expression.

4r + 8 - 8 = 24 - 8

4r = 16

Step 5 - Divide 4 on both sides in the above equation.

r = 4

The value of r is 4.

For more information, refer to the link given below:

https://brainly.com/question/1957976